The Role and Communication Competence of Agricultural Instructors on Rice Productivity Levels in Kota Manna District, South Bengkulu Regency - Kurniasih, Fenny; Lusiana Andriani Lubis; Humaizi, Humaizi (Journal of Social Interactions and Humanities, 2024)
This study aims to examine the impact of agricultural extension agents' role on the productivity of paddy fields in Kota Manna District, This research uses a quantitative approach with descriptive methods. We used single-table analysis, cross-tabulation analysis, the partial t test, the simultaneous F test, and the coefficient of determination to analyse the research data. The results confirmed the acceptance of Ha1, indicating a relationship between the role of agricultural extension workers and the productivity of paddy rice in Kota Manna Subdistrict; the acceptance of Ha2, indicating a relationship between the communication competence of agricultural extension workers and the productivity of paddy rice in Kota Manna Subdistrict; and concurrently, the acceptance of Ha3, indicating that both the role of agricultural extension workers and their communication competence have an influence on the productivity of paddy rice in Kota Manna Subdistrict. The Guilford scale categorizes the simultaneous influence of the role variable and the communication competence of agricultural extension workers as moderate or medium, indicating a relatively high impact. nstitutions, and the availability of credit.